2010
DOI: 10.1007/s00404-010-1535-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of isosorbide mononitrate and misoprostol for cervical ripening in termination of pregnancy between 8 and 12 weeks: a randomized controlled trial

Abstract: The results show that IMN has a definite role and better safety profile than misoprostol in first trimester cervical ripening, although misoprostol is more effective and causes less blood loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
1
4
1
1
Order By: Relevance
“…Isosorbide mononitrate. Similar findings have been shown by Duhan N et al 7 Abdominal pain was non significantly higher after administration of misoprostol in present study in contrast to significant high incidence of pain (17 patients v/s 55 patients) seen by Waleed-EIKhayat et al 8 Vital parameters showed no significant variation in our study. Arteago-Troncoso G et al 9 showed that systolic & diastolic blood pressures were lower after administration of tab.…”
Section: Discussioncontrasting
confidence: 56%
“…Isosorbide mononitrate. Similar findings have been shown by Duhan N et al 7 Abdominal pain was non significantly higher after administration of misoprostol in present study in contrast to significant high incidence of pain (17 patients v/s 55 patients) seen by Waleed-EIKhayat et al 8 Vital parameters showed no significant variation in our study. Arteago-Troncoso G et al 9 showed that systolic & diastolic blood pressures were lower after administration of tab.…”
Section: Discussioncontrasting
confidence: 56%
“…Dhillon et al [21] in their study involving 25 women in each group also showed that headache was statistically higher in the ISMN group than the misoprostol group. Similar findings were also shown by Duhan et al [22]. However, this present study fails to demonstrate any significantly higher incidence of headache in the ISMN group.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, there can be no comparison with data from other studies since, to our knowledge, this is the first time that an effort to estimate blood loss has been reported. However, in a study about the use of IMN for first trimester termination of pregnancy, a higher blood loss was noted in the intervention group but without any clinical significance [10].…”
Section: Discussionmentioning
confidence: 97%
“…There is now data about the use of ΝΟ donors in induction of labor [8,9] and also first trimester terminations of pregnancy [2,10]. The published results are contradictory and inconclusive.…”
Section: Introductionmentioning
confidence: 97%